2005
DOI: 10.1103/physrevb.72.024535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometrical symmetry on the angular dependence of the critical magnetic field in superconductor/normal metal multilayers

Abstract: The angular dependence of the upper critical field, H c ͑⌰͒, for Nb/ Pd multilayers with different geometrical symmetries ͑i.e., with an even or an odd number of bilayers, N bil ͒ and thickness of Nb and Pd layers of the order of superconducting coherence length were investigated ͑the angle ⌰ is here defined from the plane parallel to the sample surface͒. The presence of an angular dimensional crossover at some temperature dependent angle ⌰ * ͑T͒ was established. At angles ⌰Ͻ⌰ * ͑T͒ the multilayers are in two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…films with a thickness of a few lattice constants, the softening of the phonon spectra obtained by depositing metal nanoparticles on the film surface has been demonstrated to cause an increase of T c [16][17][18][19]. On the contrary, the quality of the surface in ultrathin superconducting films can have a strong detrimental effect on the values of the critical temperature, as observed and theoretically explained in proximity-coupled superconductor/normal metal (S/N) hybrids [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…films with a thickness of a few lattice constants, the softening of the phonon spectra obtained by depositing metal nanoparticles on the film surface has been demonstrated to cause an increase of T c [16][17][18][19]. On the contrary, the quality of the surface in ultrathin superconducting films can have a strong detrimental effect on the values of the critical temperature, as observed and theoretically explained in proximity-coupled superconductor/normal metal (S/N) hybrids [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, the quality of the surface in ultrathin superconducting films can have a strong detrimental effect on the values of the critical temperature, as observed and theoretically explained in proximity-coupled superconductor/normal metal (S/N) hybrids [20][21][22][23][24]. The Eliashberg function for Nb, measured by tunnel spectroscopy [25] and calculated with λ ≈ 1.24 and µ * ≈ 0.21 [11], reveals that the EPhI is significant in the frequency range 2-7 THz.…”
Section: Introductionmentioning
confidence: 96%
“…Since this vortex structure is related to that one of a layered superconductor (see Chap. VIII-A of the review of Blatter et al 48 ), this conclusion is supported by the investigations of Prischepa et al 92 , who found an angular dimensional cross-over of H c (θ) at fixed temperature for Nb/Pd multilayers. Samples of odd and even numbers of normal/superconducting (N/S) bilayers of Pd/Nb (9 and 10, respectively, plus a capping Pd layer) were measured in the temperature range T < T * < T c0 , where the square-root behavior of H c (T ) indicates a two-dimensional behavior (for T * < T < T c0 a linear temperature law of H c (T ) is observed, indicating threedimensionality).…”
Section: Thin Films and Layered Superconductorsmentioning
confidence: 57%
“…The latter range is interpreted as an unusual three-dimensional mode, because the large angle tail can be described by the Lawrence-Doniach model. The physical interpretation proposed is that for small angles the superconducting nucleus is localized in one period of the S/N structure, but for large angles, it is spread over more than one period by the perpendicular component of the external magnetic field, resulting in an object with a three dimensional feature (for a detailed discussion see the work of Prischepa et al 92 ). It is argued that, nevertheless, the Lawrence-Doniach description is not applicable, because it was deduced in the approximation of the homogeneous infinite medium.…”
Section: Thin Films and Layered Superconductorsmentioning
confidence: 99%
“…Apart from this, the location (relative to the domain wall) and the shape of the superconducting nuclei was studied [38]. In the case of stripe domains, when the field close to the ferromagnet can be approximated by a step function, the nucleation in the S-film is similar to the case of S/N structures (N is a normal metal) [43][44][45].…”
Section: Introductionmentioning
confidence: 99%